2020
DOI: 10.1002/aelm.202000201
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Axially Polar Ferroelectricity in a Columnar Liquid Crystal Phase by Introducing Chirality

Abstract: Axially polar ferroelectric columnar liquid crystals (AP‐FCLCs) are materials in which the molecules are self‐organized into axially polar columns and exhibit switching and holding of their polar directions. If the polar directions along the columnar axis can be controlled by using a nanosized electrode, AP‐FCLCs have the potential to realize ultrahigh‐density memory devices. Though switching polarities in columnar liquid crystal phases have been studied by many scientists, it remains difficult to realize bist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 71 publications
2
33
0
Order By: Relevance
“…In 2020, our group also reported ferroelectricity in a rather thick layer (5 μm) of a chiral urea compound, N,N′-bis(3,4,5tri(S)-citronellyloxyphenyl)urea [(S)-1] 31 (Scheme 1), which achieved both a low E c (4.12 V μm −1 ) and highly stable polarization (the polarity quantitatively remained even after 8 h). From the comparison of (S)-1 with non-chiral ureas [e.g., Urea-10 (R = (CH 2 ) 9 CH 3 )], 29,31 we concluded that the helical structure generated by the chirality played an important role in generating its unique ferroelectricity. This result was because the one-handed, tightly wound helix kept the intermolecular distances between the substituent groups short, which effectively strengthened the attractive intermolecular interactions, such as alkyl−alkyl, phenyl−phenyl, and dipole−dipole interactions, in each column.…”
Section: ■ Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…In 2020, our group also reported ferroelectricity in a rather thick layer (5 μm) of a chiral urea compound, N,N′-bis(3,4,5tri(S)-citronellyloxyphenyl)urea [(S)-1] 31 (Scheme 1), which achieved both a low E c (4.12 V μm −1 ) and highly stable polarization (the polarity quantitatively remained even after 8 h). From the comparison of (S)-1 with non-chiral ureas [e.g., Urea-10 (R = (CH 2 ) 9 CH 3 )], 29,31 we concluded that the helical structure generated by the chirality played an important role in generating its unique ferroelectricity. This result was because the one-handed, tightly wound helix kept the intermolecular distances between the substituent groups short, which effectively strengthened the attractive intermolecular interactions, such as alkyl−alkyl, phenyl−phenyl, and dipole−dipole interactions, in each column.…”
Section: ■ Introductionmentioning
confidence: 96%
“…The AP-FCLC phase has the potential to realize writable, rewritable, and nonvolatile nano-sized memory devices if one-bit of information can be recorded by a nano-sized electrode. 2,4,31 However, it is still challenging to maintain the induced polarization after removal of the electric field, and we believe that polarization maintenance is most important to realize nonvolatile memory devices.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations